2011
DOI: 10.1007/s11340-010-9459-7
|View full text |Cite
|
Sign up to set email alerts
|

Grid Method for Microscale Discontinuous Deformation Measurement

Abstract: The objective of this paper is to explore both grid method and Digital Image Correlation (DIC) technique for microscale and discontinuous displacement measurements, such as those associated with crack tips. First, the principle of the grid method is revisited. The grid method and DIC technique are then applied to computer generated images to calculate the displacement field around crack tips. Finally, the grid method is applied to actual experimental images of fracture tests which are conducted inside a Scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Even though the progressive dissemination of affordable digital cameras and powerful computational resources together with recent advances in image processing led finding the coordinates of the points automatically and more precisely than by hand , this technique was mainly used for measuring large displacements and strains like those occurring in composite or metal sheet forming . It is now only scarcely mentioned in recent papers such as and seems to fall progressively into disuse. The main cause is the emergence and dissemination of DIC in the experimental mechanics community .…”
Section: The Grid Method: What Are We Talking About?mentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the progressive dissemination of affordable digital cameras and powerful computational resources together with recent advances in image processing led finding the coordinates of the points automatically and more precisely than by hand , this technique was mainly used for measuring large displacements and strains like those occurring in composite or metal sheet forming . It is now only scarcely mentioned in recent papers such as and seems to fall progressively into disuse. The main cause is the emergence and dissemination of DIC in the experimental mechanics community .…”
Section: The Grid Method: What Are We Talking About?mentioning
confidence: 99%
“…The zone underneath the mesh bars was not coated contrary to the space inside each grid, thus generating regular arrays of spots. Pitches equal to 12.5 μ m are reported in , but other pitch values can potentially be obtained with the same technique: from 12.5 to 500 μ m in .…”
Section: Marking Surfaces With Gridsmentioning
confidence: 99%
“…Jin et al [27] investigated both the grid method and the DIC technique to measure the discontinuous displacement field around the tip of a propagating crack at relatively low magnifications. The applied deformation was in the range of linear elastic deformation and no quantitative comparison was made between the results obtained from DIC and those obtained with their grid technique.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Jin et al (2011) have shown that both the grid method and DIC can be used simultaneously for microscale deformation measurements. Lord et al (2010) reviewed the experimental techniques for miniaturized testing for strength and strain measurement, and detailed the evolution and strengths of the DIC method.…”
Section: Introductionmentioning
confidence: 99%